Pendampingan Pengabdian Kepada Masyarakat Bagi Pengrajin Limbah Jagung di Kabupaten Pati - Sri Mulyani; Budi Gunawan; Mukhamad Nurkamid (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
There are many types of handicrafts from Pati Regency, one of which is corncob crafts whose raw materials come from unused corn waste. The corncobs are processed into various forms of crafts including night lamps, watches, tissue holders, jars, flower holders, wall hangings and much more. The COVID-19 pandemic caused SMEs to experience a decline in sales. In order to help increase sales, the service team carried out several mentoring activities. Some of the mentoring activities carried out are providing training and e-marketing assistance, determining selling prices, and recording financials through the android application. Participants in community service activities are UKM "Tyara Craft" located in the Sarirejo area, Pati Regency. This series of service activities was carried out on March 16 to June 8, 2021. The methods taken in this service activity include interviews, observations, lectures, tutorials, discussions, mentoring, and evaluations. After three months of mentoring, the partner finally has an online sales booth, can determine the exact selling price and make financial records through the Lamikro android application.